Politeness Strategies Used in Javanese Wedding Ceremony - Ika Agustina; Sumarsih Sumarsih; Busmin Gurning (Universitas Negeri Medan, 2015)
This study deals with Politeness Strategies Used in Javanese Wedding Ceremony. The objectives of the study were to identify types of Politeness strategies and the pattern of strategies used in Javanese wedding ceremony. The approach used in this study are based on Politeness theory by Brown and Levinson (1987); Bald on record, Positive politeness, Negative politeness and Off-record strategy. This study employed descriptive qualitative design. The data were the transcriptions of recorded observation and interview. The data were taken from observation using audio visual recorder in Javanese wedding ceremony of Dina Wagiani and Oman Syahputra especially in some events which were Peningsetan (17th March 2012), Midodaremi (14th April 2012), Panggih (15th April 2012) dan Sungkeman (15th April 2012) that are held in Medan located at Jl. Marelan II Pasar IV, Kelurahan Rengas Pulau, Kecamatan Medan Marelan. The finding showed that all the types of Politeness strategies were applied in Javanese wedding ceremony. The percentage of positive politeness was 54.21%, bald- on record was 33.16%, negative politeness was 8.95% and off-record was 3.68%. The most dominant type of politeness strategies used was positive politeness strategy. It was used because Javanese people try to satisfy the hearer and avoid conflicts with other people. They also applied it to make both families get closer each other, so there was no distance between them. They endeavor to maintain social harmony and solidarity between bride‘s family and bridegroom‘s family during wedding ceremony.